2007
DOI: 10.3343/kjlm.2007.27.5.324
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Positive Results in Mediace Rapid Plasma Reagin and Treponema pallidum Latex Agglutination as the Automated Syphilis Test

Abstract: Background : We compared the results of automated and quantitative methods for the diagnosis of syphilis, Mediace Rapid Plasma Reagin (RPR) and Mediace Treponema pallidum Latex Agglutination (TPLA) (Sekisui Chemical Co., Ltd, Japan) with those of conventional methods.Methods : Sera from 3,896 persons who had health checkups between December 2005 and November 2006 were included in the evaluation of positive rates and biological false positives (BFP) for Mediace RPR and TPLA. In addition, 134 patients' sera posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…However, at least one automated spectrophotometric non‐treponemal test has been developed and used in, e.g. Korea, and this and similar methods would be valuable to evaluate internationally. On the contrary, there are a number of internationally available automated treponemal antibody assays.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, at least one automated spectrophotometric non‐treponemal test has been developed and used in, e.g. Korea, and this and similar methods would be valuable to evaluate internationally. On the contrary, there are a number of internationally available automated treponemal antibody assays.…”
Section: Discussionmentioning
confidence: 99%
“…An assay with an independent reading procedure, such as an EIA assay that is read on a spectrophotometer, would be preferable. However, despite some attempts to develop such assays no effective and strictly evaluated non‐treponemal EIA is commercially available internationally. Nevertheless, the IgM treponemal assays have been used to identify active syphilis.…”
Section: Discussionmentioning
confidence: 99%
“…The confirmation test by ESP-LINE TP need in the samples reacted by Mediace TPLA, not all samples. Furthermore, another study reported that, owing to its ability to detect IgM, Mediace TPLA could detect infection earlier than EIA or CIA [15]. Together with its ease of use, these qualities lead us to recommend Mediace TPLA for use in initial screening tests.…”
mentioning
confidence: 99%